Investigating antimicrobial compounds in South African Combretaceae species using a biochemometric approach. (6th April 2021) - Anokwuru, Chinedu P.; Sandasi, Maxleene; Chen, Weiyang; van Vuuren, Sandy; Elisha, Ishaku L.; Combrinck, Sandra; Viljoen, Alvaro M.
Abstract: Ethnopharmacological relevance: Many species within the family Combretaceae are popular medicinal plants that are used traditionally to treat various conditions, of which many are related to bacterial infections. Global concerns regarding the increasing resistance of pathogens towards currently available antibiotics have encouraged researchers to find new drugs with antibacterial activity, particularly from plant sources. Aim of the study: This study was aimed at exploring the broad-spectrum antibacterial potential of methanol extracts of species representing four genera of Combretaceae ( Combretum, Pteleopsis, Quisqualis, Terminalia ), indigenous to South Africa, using a biochemometric approach. Materials and methods: The microdilution assay was used to determine the antibacterial activities, measured as minimum inhibitory concentrations (MICs), of the 51 methanol extracts representing 35 Combretaceae species, against nine species of pathogenic bacteria. Integrative biochemometric analysis was performed, thereby correlating the MIC values with the metabolomic data obtained from ultra-performance liquid chromatography-mass spectrometry (UPLC-MS) analysis. Orthogonal projections to latent structures-discriminant analysis (OPLS-DA) models were constructed for six pathogens displaying variation in their susceptibility towards the extracts. Results: Evaluation of the overall MIC values obtained indicated that extracts of species from the four genera displayed the highest activity towards Bacillus cereus ATCC 11778 (average MIC 0.52 mg/mL) and Salmonella typhimurium ATCC 14028 (average MIC 0.63 mg/mL). These bacteria were the most sensitive Gram-positive and Gram-negative bacteria, respectively. Extracts from Combretum acutifolium, Combretum imberbe and Combretum elaeagnoides were the most active, with average MIC values of 0.70 mg/mL, 0.52 mg/mL and 0.45 mg/mL, respectively. Five triterpenoid compounds were tentatively identified as biomarkers from the biochemometric analysis. Conclusion: Correlation of the phytochemistry of species from four genera in the Combretaceae family with antibacterial activity revealed that triterpenoids are responsible for the broad-spectrum antibacterial activity observed. Graphical abstract: Image 1 Highlights: Ethnopharmacological approach to antibacterial activity of four Combretaceae genera. Combretum species displayed the highest antibacterial activities. Combretum acutifolia, C. imberbe and C. eleagnoides have broad spectrum potential. Bacillus cereus and Salmonella typhimurium were the most susceptible pathogens. Biochemometrics revealed the triterpenoids as the bioactive compounds.